Effectiveness of Extracts of Garlic (Allium sativum L) and Red Ginger (Zingiber officinale var rubra) as Escherichia coli Control in Broiler Chicken - R N Damanik; M Tafsin; A H Daulay; E Mirwandhono; T H Wahyuni (Talenta Publisher, 2017)
This study aims to determine the effectiveness of extracts of garlic (Allium sativum L.) and ginger (Zingiber officinale) on the growth of broiler chickens infected with E. coli. The design used in this study was a Completely Randomized Design with 6 treatments and 3 replications. The treatment consisted of P0A = control without infection, P0B = control + E. coli infection, P1 = E. coli infection + 0.05% tetracycline antibiotics, P2 = E. coli infection + 1% garlic (Allium sativum L.) extract , P3 = E. coli infection + 1% ginger (Zingiber officinale) extract and P4 = E. coli infection + garlic (Allium sativum L) extract and 1% ginger (Zingiber officinale). The results showed that the administration of garlic and ginger extract had a significant effect (P <0.05) on the decrease in the number of Escherichia coli bacteria in broiler chicken feces. The combination of extracts of garlic (Allium sativum L.) and red ginger (Zingiber officinale) has the most effective effect compared to garlic and ginger extract alone. It was concluded that the administration of extracts of garlic and ginger could be used as Escherichia coli control in broiler chickens.